The HALP Index Is Associated with the Recurrence of Persistent Atrial Fibrillation Following Radiofrequency Catheter Ablation - Wang Z; Qu Y; Wang H; Wang C (Journal of Inflammation Research)
Zhen Wang,1 Yilin Qu,2 Hua Wang,1 Chunxiao Wang1 1Department of Cardiology, Yantai Yuhuangding Hospital of Qingdao University, Yantai, People’s Republic of China; 2Department of Medical Records, Yantai Yuhuangding Hospital of Qingdao University, Yantai, People’s Republic of ChinaCorrespondence: Chunxiao Wang, Email 330148640@qq.comPurpose: To evaluate the relationship between the HALP Index and the recurrence of persistent atrial fibrillation (AF) following radiofrequency catheter ablation (RFCA).Methods: We retrospectively analyzed 471 patients with persistent AF treated with RFCA between January 2019 and June 2022 at Yantai Yuhuangding Hospital of Qingdao University. The relationship between the Hemoglobin, Albumin, Lymphocyte, and Platelet (HALP) Index and AF recurrence outcomes was assessed using Kaplan-Meier survival curve analysis and multifactorial Cox proportional hazards regression modeling. Receiver operating characteristic (ROC) curves were generated to evaluate the predictive value of the HALP Index for recurrence in patients with persistent AF undergoing RFCA.Results: After a mean follow-up of 43.6 months, recurrence occurred in 130 patients (27.6%). There was a significant difference in the recurrence rate after RFCA of AF among the different HALP Index groups (44.9% vs 26.3% vs 22.9% vs 16.2%, F = 9.347, P < 0.001). Multifactorial Cox proportional hazards regression analysis indicated that the HALP Index was significantly associated with recurrence after RFCA of AF (HR = 0.967, P < 0.001). The HALP Index was treated as a categorical variable in the multifactorial Cox proportional hazards regression analysis, which revealed that the recurrence rate of RFCA of AF was significantly higher in the low HALP Index group compared to the high HALP Index group (HR = 6.080, P < 0.001). The results of the Kaplan-Meier survival analyses suggested a significant difference in recurrence after RFCA of AF among the various HALP Index groups (Log-rank P < 0.001). The ROC curve analysis demonstrated the predictive value of the HALP Index for recurrence after RFCA of AF, with an area under the curve (AUC) of 0.659 (95% CI 0.603– 0.715, P < 0.001).Conclusion: The HALP Index was an independent protective predictor of recurrence following RFCA of persistent AF.Keywords: the HALP index, atrial fibrillation, radiofrequency catheter ablation, recurrence